Do events contribute to the brand of Novi Sad? A millennials` perspective - Jojić Novaković, Đurđica; Mandarić, Marija (Hotel and Tourism Management, 2019)
In the era of the global economy and more expressed need for obtaining a competitive advantage, strong brands and the branding process itself gain importance, which is why brand management principles are being applied even to geographical areas and destinations. Events and festivals represent an important element of brand destination, i.e. of cities worldwide, whereas in strategic documents related to the tourism both of the Republic of Serbia and of the city of Novi Sad, they are recognised as priority tourist products. The topic of this research is the analysis of importance of festivals for the "city of festivals" i.e. Novi Sad, but from the point of view of population that had little attention of researchers – millennials. Millennials, i.e. those born in the 1990’s, are the largest generation humankind ever had and their attitudes are dominating on the market. The research conducted in May 2018 on a sample of 102 students in Novi Sad has shown absolute domination of Exit festival in all aspects, but also some other interesting characteristics of Novi Sad brand.